The Results and Prospects for Further Development of the System of Means for Prevention and Liquidation of Emergency Situations in the Republic of Belarus - Bariev Энвер Ризаевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
At present time the maintenance of safety requires not only creation of bodies, ways and means for the defense from various kinds of danger, but also creations of social and economic mechanism. From this point of view the problem of safety maintenance of the society should be considered in close connection with the problem of its move to stable development.